Regulation of Phenolic Compound Production by Light Varying in Spectral Quality and Total Irradiance - Pech, Radomír; Volná, Adriana; Hunt, Lena; Bartas, Martin; Červeň, Jiří; Pečinka, Petr; Špunda, Vladimír; Nezval, Jakub (International journal of molecular sciences, 2022)
Photosynthetically active radiation (PAR) is an important environmental cue inducing the production of many secondary metabolites involved in plant oxidative stress avoidance and tolerance. To examine the complex role of PAR irradiance and specific spectral components on the accumulation of phenolic compounds (PheCs), we acclimated spring barley (Hordeum vulgare) to different spectral qualities (white, blue, green, red) at three irradiances (100, 200, 400 µmol m-2 s-1). We confirmed that blue light irradiance is essential for the accumulation of PheCs in secondary barley leaves (in UV-lacking conditions), which underpins the importance of photoreceptor signals (especially cryptochrome). Increasing blue light irradiance most effectively induced the accumulation of B-dihydroxylated flavonoids, probably due to the significantly enhanced expression of the F3'H gene. These changes in PheC metabolism led to a steeper increase in antioxidant activity than epidermal UV-A shielding in leaf extracts containing PheCs. In addition, we examined the possible role of miRNAs in the complex regulation of gene expression related to PheC biosynthesis.
Keywords: fenoly; flavonoidy; Flavonoids; Light; photoprotection; Phenols; ječmen (rod); listy rostlin; antioxidants; secondary metabolism; UV tolerance; spring barley (Hordeum vulgare); Hordeum; ultrafialové záření; miRNA; transcriptomics; světlo; Plant Leaves; flavonoids; HPLC; Ultraviolet Rays; spectral quality of light